THZ1 targeting CDK7 suppresses STAT transcriptional activity and sensitizes T-cell lymphomas to BCL2 inhibitors - Cayrol, María Florencia (2017)
Fil: Caryrol, Florencia. Weill Cornell Medicine. Hematology and Oncology Division. Department of Medicine; Estados Unidos